2006
DOI: 10.1111/j.1365-2826.2006.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Time‐Specific Effects of Perinatal Glucocorticoid Treatment on Anterior Pituitary Morphology, Annexin 1 Expression and Adrenocorticotrophic Hormone Secretion in the Adult Female Rat

Abstract: Perinatal glucocorticoid (GC) treatment is increasingly associated with long-term disturbances in hypothalamo-pituitary-adrenocortical function. In the male rat, such treatment induces profound molecular, morphological and functional changes in the anterior pituitary gland at adulthood. To determine whether these effects are sex-specific, we have examined the effects of perinatal dexamethasone treatment on the female pituitary gland, focusing on (i) the integrity of the annexin 1 (ANXA1) dependent regulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 68 publications
(94 reference statements)
1
2
0
Order By: Relevance
“…In addition, the ACTH-induced enhancement of plasma corticosterone levels in RU-38486-treated mice was lower than that observed in vehicle-treated mice (Fig. 1), which reinforces the role of glucocorticoid actions on HPA axis (30,41,55) and shows the genomic pathway on the effect. Four hours after ACTH injection, mature neutrophils were mobilized from the bone marrow into the blood, as detected by the reduced numbers of mature granulocytes in the bone marrow ( Fig.…”
Section: Resultssupporting
confidence: 67%
“…In addition, the ACTH-induced enhancement of plasma corticosterone levels in RU-38486-treated mice was lower than that observed in vehicle-treated mice (Fig. 1), which reinforces the role of glucocorticoid actions on HPA axis (30,41,55) and shows the genomic pathway on the effect. Four hours after ACTH injection, mature neutrophils were mobilized from the bone marrow into the blood, as detected by the reduced numbers of mature granulocytes in the bone marrow ( Fig.…”
Section: Resultssupporting
confidence: 67%
“…A programmed increase in responsiveness of the rat adrenal to stress is in line with previous reports showing enhanced activity of the adult HPA axis at both the hypothalamic and pituitary levels after fetal glucocorticoid excess. Thus, Shoener et al (2006) reported elevated expression of hypothalamic CRH in adult offspring of dexamethasone-treated mothers, and perinatal dexamethasone treatment was shown to increase pituitary corticotroph number in female offspring ( John et al 2006). Our observation that adrenal Mc2r expression is elevated in offspring of dexamethasone-treated mothers suggests that an enhanced HPA reactivity also involves greater responsiveness at the level of the adrenal (i.e.…”
Section: Discussionmentioning
confidence: 68%
“…In addition, FS cells show high annexin A1 (ANXA1) levels, which is comparable to non-endocrine cells of the hypothalamus ( 139 ). Since glucocorticoids increase ANXA1 expression in FS cells, it is hypothesized that ANXA1 + FS cells subsequently regulate corticotrophs, which express ANXA1-associated G protein coupled receptors, via a paracrine mechanism ( 139 141 ). In the pars tuberalis , FS cells are localized in close association with GnRH-containing axon terminals, which regulate seasonal reproduction and photoperiodicity.…”
Section: Hh Signaling In the Pituitary Glandmentioning
confidence: 99%